A new series of corpus presentations - Sering, Konstantin; Bowie, David; Gerstenberg, Annette (Journal of Language and Aging Research, 2024)
The Journal of Language and Aging Research (JLAR) presents a new series of corpus presentations. The series is meant to feature research data suitable for analyzing the processes and manifestations of linguistic aging. Dedicated to the idea of open science, data are presented with regard to the principles of findability, availability, interoperability, and reusability (FAIR). Limitations of open access due to ethical concerns and possible other limitations are discussed. The series of corpus presentations allows for a standardized introduction of newly conceived or established datasets, promotes the exchange, on an empirical basis, of Language and Aging Research (LAR), stimulates the discussion of standards in Research Data Management (RDM), and motivates the further development and sharing of resources and techniques within the community. Faced with age-related bias in artificial intelligence and with copyright issues, settling the provenance of datasets representing older adults and guaranteeing their originality holds immense significance.